Improving Air Force Depot Programming by Linking Resources to Capabilities - Snyder, Don (RAND Corporation, 2012)
Depot purchased equipment maintenance (DPEM) funds the bulk of the work done at Air Force depots that does not involve the repair of spares or work on modification programs. This report analyzes how to better program for DPEM, emphasizing the importance of defining metrics that relate directly to objectives in operational plans and that are defined broadly enough to embrace a range of funding areas.